IMPLEMENTATION OF THE RIGHTS AND OBLIGATIONS OF PUBLIC AND PRIVATE GENERAL HOSPITALS IN MAKASSAR - Andi Muhammad Sofyan; Muhammad Djaelani Prasetya; M. Aris Munandar; Muhammad Ihsan (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This study examines the extent to which the implementation of the rights and obligations of Public and Private General Hospitals in Makassar City and the obstacles that make these rights and obligations difficult to implement. The research method used in this study is the empirical method. The results of this study indicate that the implementation of the rights and obligations at the Regional General Hospital (Rumah Sakit Umum Daerah/RSUD) of Makassar City and the Mother and Child Hospital (Rumah Sakit Ibu dan Anak/RSIA) Ananda has carried out the rights and obligations of the hospital simultaneously. However, in the implementation of these rights and obligations, there are still several obstacles, such as community habits, administrative completeness that does not meet minimum service standards, and other supporting infrastructure. Especially for Makassar City Hospital, the data for health personnel has not been updated as mandated by the Government Regulation on the Implementation of the Hospital Sector. Meanwhile, RSIA Ananda must improve the facilities and infrastructure of the hospital parking lot so that health services can be more optimal and effective, and efficient to carry out.